2020
DOI: 10.1108/tr-10-2019-0406
|View full text |Cite
|
Sign up to set email alerts
|

Competitor intelligence and analysis (CIA) model and online reviews: integrating big data text mining with network analysis for strategic analysis

Abstract: Purpose This study aims to propose a competitor intelligence and analysis (CIA) model that can be used for the analysis of a firm’s competitors. Empirically, it investigates the application of the CIA model on online reviews. This proposed model clarifies the confusion between terms such as competitive intelligence, competitor intelligence and competitor analysis and provides a more efficient process for managers. Design/methodology/approach The approach of the model integrates text mining techniques as a bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 91 publications
3
16
0
Order By: Relevance
“…Previous studies have also identified a significant occurrence of the attribute "breakfast" in reviews (Köseoglu et al, 2019;Xu & Li, 2016). As in this study, the "breakfast" attribute was linked to positive reviews (B.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Previous studies have also identified a significant occurrence of the attribute "breakfast" in reviews (Köseoglu et al, 2019;Xu & Li, 2016). As in this study, the "breakfast" attribute was linked to positive reviews (B.…”
Section: Discussionsupporting
confidence: 73%
“…This attribute was also identified as an important subject by several studies (B. Kim et al, 2016;Köseoglu et al, 2019;Padma & Ahn, 2020;Sann & Lai, 2020a;Xu & Li, 2016;Ying et al, 2020) and, as in this paper, its occurrence was mostly associated with positive reviews (Alrawadieh & Law, 2019;Brochado & Brochado, 2019;Wu et al, 2017).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…This study aims to identify the satisfied and dissatisfied factors of heritage hotels by analyzing online reviews written by customers on the third-party website. Hotels use online reviews to apply the business intelligence techniques to understand the customers’ preferences, opinions on service offerings (Köseoglu et al , 2020; Köseoglu et al , 2019) and to gain the competitive advantage by offering innovative services and products (Kandampully and Solnet, 2019; Köseoglu et al , 2019; Leung, 2019). We chose TripAdvisor as a data source for this study because of its popularity in the hospitality industry (Filieri et al , 2015; Xie et al , 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Customers express their experiences, recommendations and opinions about the product/service in reviews on webpages, blogs, forums, mobile applications and social network sites (Yoo and Gretzel, 2011). Online reviews are a part of eWOM (Köseoglu et al , 2020; Liu et al , 2019; Xu and Li, 2016). Online reviews create an opinion, provide user information and help in the decision-making process for potential buyers (Helversen et al , 2018).…”
Section: Introductionmentioning
confidence: 99%